Etho-ecological studies of Teal wintering in the Camargue (Rhone Delta, France) - Tamisier, Alain (Wildfowl, 1974)
The Camargue, with 120,000-150,000 wintering ducks, 40,000 of them Teal Anas crecca, is one of the most important winter quarters for Western Palaearctic Anatidae. The previously published results of a long term study (1964-1972) about Teal are outlined. Ringing results have shown that this population’s breeding area ranges from Finland to the Urals. Most of it winters in the Camargue. Only in a cold spell do they fly westwards to the Atlantic coasts. Data are given on variation of numbers, mortality rates, sex-ratio and age-ratio. The different types of behaviour are analysed (sleeping, preening, swimming and feeding) and their diurnal duration measured. For each month (August-March) the exact composition of the daily cycle (diurnal and nocturnal activities) is known. The wintering period is divided into three successive phases, varying in the composition of the daily cycle. Feeding behaviour, diet, and biomass of the available food are analysed. The daily feeding duration varies through the months with the physiological condition of the Teal and with climatic factors. There is always plenty of food available. Under former natural conditions the limiting factors of the population were probably low water levels (beginning of the winter) and low temperatures (end of the winter). Their effects are today concealed by those of hunting mortality which very likely regulates the numbers of Teal wintering in the Camargue. Wintering Teal are gregarious by day and scatter at night for feeding. Many feeding grounds are linked to each daytime haunt, constituting a ’functional unit’ always exploited by the same birds. In the Camargue three or four such units show very little overlap. The diurnal gregarious habit is shown as an adaptation to predation pressure, and not as a response to human disturbance. It enforces nocturnal feeding. This alternation is strengthened by some other secondary factors.